A study of loss and gain of meaning in the vietnamese translational version of uncle tom’s cabin by harriet beecher stowe - Nguyễn,Cao Phước Tùng (2016)
The thesis identifies and analyzes common cases of loss and gain in meaning in Vietnamese translational version of Uncle Tom’s Cabin by Harriet Beecher Stowe. Five chapters are included in the thesis. The analysis is made on bilingual presentation in which English is the soucre language and Vietnamese is the target one. The descriptive and comparitive methods in comparision with approaches of quantitative and the qualitative are used in analyzing findings which are 200 samples of loss and gain of meaning collected from the novel Uncel Tom’s Cabin and from the Vietnamese translational version. The discussions on these findings are to show the common cases of loss and gain in meaning Vietnamese translational version of Uncle Tom’s Cabin by Harriet Beecher Stowe as well as to find out the way how meaning can be lost and gained through translation process. Hopefully, the findings and discussion in the thesis will partly contribute to further research, and to teaching and learning of English – Vietnamese translation.